THE DOMINANCE OF LOCAL CULTURE AND RELIGIOUS DOGMA OVER STATE LAW: A STUDY OF CHILD MARRIAGE LEGAL CULTURE IN RURAL INDONESIA - Aziz, Muhammad; Sholikah, Sholikah; Ghazali, Mohd Fahmi; Lee, Umi Hamidaton Mohd Soffian; Zakiyah, Amanatus (Study Program of Islamic Family Law, Syari'ah Faculty, University of Al-Hikmah Indonesia, 2025)
The phenomenon of child marriage in rural Indonesia is a complex socio-legal issue, characterized by tensions between state legal norms, customary traditions, and interpretations of religious dogma. Although Law No. 16/2019 has raised the minimum age for marriage for men and women to 19 years with the noble aim of protecting children's rights, the reality on the ground shows a high number of requests for marriage dispensations that actually legitimize this practice. This study aims to analyze the dominance of customary law and religious dogmatism over state law in the context of child marriage through the framework of Lawrence M Friedman's Legal System Theory. Using qualitative socio-legal research methods, this study examines the dynamic interaction between legal substance, legal structure, and legal culture.